Implementation of the Compulsory Nine-Year Basic Education Program: Opportunities and Constraints at Household and Community Level - Titik Handayani; Soewartoyo Soewartoyo; Makmuri Sukarno (Deputy of Social Sciences and Humanities, the Indonesia Institute of Sciences (LIPI), 2009)
-